Audiologic Monitoring for Potential Ototoxicity in a Phase I Clinical Trial of a New Glycopeptide Antibiotic - Campbell, Kathleen C.M.; Kelly, Ellen; Targovnik, Nan; Hughes, Larry; Van Saders, Claudia; Gottlieb, Alice Bendix; Beth Dorr, Mary; Leighton, Anton (Journal of the American Academy of Audiology, 2003)
This study describes audiologic methodology and results for evaluating potential ototoxicity in a phase I clinical trial of a new glycopeptide. This study was conducted under good clinical practices, which are regulated by the US Food and Drug Administration (FDA) (21 Code of Federal Regulations), and input from the FDA was sought prior to study implementation. Healthy, normal volunteers underwent extensive medical and audiologic assessments as part of this phase I dose- escalation study of dalbavancin, a new glycopeptide, to assess potential side effects. Audiologic monitoring included air-conduction thresholds in the conventional (0.25-8 kHz) and high-frequency (10-16 kHz) ranges. At baseline, subjects were also tested using word recognition, bone conduction testing if indicated, and tympanometry. Full testing was to be repeated if any subject met the American Speech-language-Hearing Association (ASHA) 1994 criteria for ototoxic change. However, no subjects demonstrated ototoxic change after receiving dalbavancin, nor were any false-positive results obtained.
Keywords: Audiologic monitoring; clinical trials; dalbavancin; glycopeptide; high-frequency audiometry; ototoxicity monitoring; phase I; FDA